CHILDHOOD MALTREATMENT AMONG UNDERGRADUATES OF EBONYI STATE UNIVERSITY, ABAKALIKI: PREDICTIVE ROLES OF ALCOHOLIC CONSUMPTION, PERSONALITY AND LONELINESS - OFOKE, Sunday M; UDECHUKWU, Chinwe C.; IBE, Chidebere J.; NWONYI, Sampson .K.; EZE, Linda C; OKO, Felix Uchenna (EBSU Journal of Social Sciences and Humanities, 2024)
This study investigated Childhood maltreatment among undergraduates of Ebonyi State University, Abakaliki: predictive roles of alcoholic consumption, personality and loneliness. A total of 300 participants comprising undergraduates were tested from Ebonyi State University, Abakaliki. Their ages ranged between 18 to 30 years with a mean of 24.32. The study adopted a cross sectional survey design. The four instruments used for data collection includes: childhood maltreatment inventory, big five personality inventory, alcoholic consumption and loneliness scales. Stepwise multiple regression were used to test the stated hypothesis and results indicated that personality profiling: extraversion, neuroticism, openness to experience, alcoholic consumption and loneliness statistically and significantly predict childhood maltreatment. Agreeableness and conscientiousness do not statistically and significantly predictors of childhood maltreatment. The study concludes that school management, parent should always deem it necessary to understand alcoholic consumers and personality profiling of persons that are susceptible to childhood maltreatment. The study recommends that personality assessment form should be integrated during student admission processes, especially for students who have risk factors for alcohol consumers and with past history of childhood maltreatment.